STRUCTURAL STYLE AND DEPOSITIONAL HISTORY OF THE SEMANGKO PULL APART BASIN IN THE SOUTHEASTERN SEGMENT OF SUMATRA FAULT ZONE - Maruf M Mukti (Indonesian Institute of Sciences, 2018)
Re-examination of published seismic data in the southeasternmost segment of the active Sumatra Fault zone (SFZ) reveals the characteristics of structural style and depositional history of Semangko pull apart basin (SPB). The SPB have been developed as a transtensional pull apart basin resulted from stepping over of the Semangko to Ujung Kulon segments of the SFZ. The geometry of SPB is of rhomboidal shape characterized by dual depocenters separated by a discrete structural high in the center of SPB. Based on the determination of pre- and syn-kinematic strata related to the formation of SPB, sedimentary units prior to deposition of Unit 3 can be regarded as pre-kinematic strata, whereas the syn-kinematic strata is represented by Unit 3. The basin sidewall faults of the SPB are likely to have been developed as en-echelon side wall faults and identified as the East Semangko Fault (ESF) and Kota Agung – South Panaitan Faults (KAF-SPF) in the western and eastern margin of the SPB, respectively. The development of discrete highs along the center of the SPB may relate to the formation of en-echelon cross-basin faults that are now overprinted by volcanic activity or magmatic intrusion.Analisa ulang data seismik yang telah dipublikasikan di daerah segmen paling tenggara dari zona sesar aktif Sumatra (SFZ) mengungkapkan karakteristik struktur dan sejarah pengendapan dari cekungan pull-apart Semangko (SPB). SPB terbentuk sebagai cekungan transtensional pull-apart yang dihasilkan dari step over segmen Semangko dan segmen Ujung Kulon. Geometri SPB adalah bentuk rhomboidal yang dicirikan oleh dua depocenter yang dipisahkan oleh struktur tinggian yang tidak menerus di bagian tengah SPB. Berdasarkan penentuan unit pre- dan syn-kinematic strata yang terkait dengan pembentukan SPB, unit sedimen yang terbentuk sebelum pengendapan Unit 3 dapat dianggap sebagai pre-kinematic strata, sedangkan syn-kinematic strata diwakili oleh Unit 3. Sesar side-wall dari SPB kemungkinan telah berkembang sebagai sesar yang bersifat en-echelon dan diidentifikasi sebagai Sesar Semangko Timur (ESF) dan Sesar Kota Agung - Panaitan Selatan (KAF-SPF) di tepian barat dan timur SPB. Pembentukan tinggian yang tidak menerus di sepanjang bagian tengah SPB berhubungan dengan pembentukan sesar-sesar cross-basin yang bersifat en-echelon yang sekarang telah tertutupi jejaknya oleh aktivitas gunung api atau intrusi magmatik.